1638c Particles at work – and everywhere else. (24th April 2018) - Hellebust, Stig; Wenger, John; Sodeau, John
Abstract : Airborne Particulate Matter (PM) is ubiquitous in both indoor and outdoor environments. Its adverse effect on human health is well known and is associated with both size and composition of particles. PM is a complex and heterogenous mixture, including a range of both toxic and non-toxic chemical compounds. These materials can penetrate in the human respiratory tract with the possibility to cause respiratory and heart related illnesses. Small particulate pollution has health impacts even at very low concentrations – no threshold has been identified below which no damage to health is observed. WHO estimates that in 2012 around 1 in 8 deaths were attributed to exposure to air pollution, making it the number one environmental risk factor for ill health. Particulate matter (PM) constitute a principal component of residential indoor air pollution and have been linked with both acute effects, such as irritation in the skin, eyes, nose and throat and upper airways, and chronic health effects including asthma and cardiac disease. It is also of concern in many workplace environments across a wide range of industries and sectors. Wood dust, especially hardwood dust, has been known to cause health problems and cancers in workers. Aerosols from cleaning spray products pose a threat to cleaning workers. In the ceramic sector workers can be exposed to a wide variety of powdered materials with different characteristics and chemical compositions during the manufacturing cycle (handling, materials preparation, bag filling, tiles production or cleaning processes, among others). Cooking aerosols are emitted in high concentrations from processes like frying and charbroiling, exposing kitchen and restaurant workers to high levels of airborne organic aerosols. Nanoparticles is a relatively new and little understood threat to both manufacturing and laboratory workers, and it is not known how many escape to the wider environment. Any workshop environment may contain high levels of particles in the indoor air, as will construction environments, where workers may potentially be exposed to a range of materials, including asbestos particles. Even office workers occupying near-road premises can experience high levels of toxic particles from vehicle emissions. Furthermore, bioaerosols are a class of atmospheric particles that include bacteria, viruses, pollen and fungal spores, algae, plant debris, proteins, etc. This class of particles can also have an impact on public health, as they have been associated with infectious diseases, allergies, acute toxic effects and even cancer.